LncRNA VEAL2 regulates PRKCB2 to modulate endothelial permeability in diabetic retinopathy. (28th June 2021) - Sehgal, Paras; Mathew, Samatha; Sivadas, Ambily; Ray, Arjun; Tanwar, Jyoti; Vishwakarma, Sushma; Ranjan, Gyan; Shamsudheen, K V; Bhoyar, Rahul C; Pateria, Abhishek; Leonard, Elvin; Lalwani, Mukesh; et al.
Abstract: Long non‐coding RNAs (lncRNAs) are emerging as key regulators of endothelial cell function. Here, we investigated the role of a novel vascular endothelial‐associated lncRNA ( VEAL2 ) in regulating endothelial permeability. Precise editing of veal2 loci in zebrafish ( veal2 gib005Δ8/+ ) induced cranial hemorrhage. In vitro and in vivo studies revealed that veal2 competes with diacylglycerol for interaction with protein kinase C beta‐b (Prkcbb) and regulates its kinase activity. Using PRKCB2 as bait, we identified functional ortholog of veal2 in humans from HUVECs and named it as VEAL2 . Overexpression and knockdown of VEAL2 affected tubulogenesis and permeability in HUVECs. VEAL2 was differentially expressed in choroid tissue in eye and blood from patients with diabetic retinopathy, a disease where PRKCB2 is known to be hyperactivated. Further, VEAL2 could rescue the effects of PRKCB2‐mediated turnover of endothelial junctional proteins thus reducing hyperpermeability in hyperglycemic HUVEC model of diabetic retinopathy. Based on evidence from zebrafish and hyperglycemic HUVEC models and diabetic retinopathy patients, we report a hitherto unknown VEAL2 lncRNA‐mediated regulation of PRKCB2, for modulating junctional dynamics and maintenance of endothelial permeability. Synopsis: Protein kinase C beta (PRKCB) promotes vascular permeability, and its hyper‐activation has been linked to diabetic retinopathy. Here, the novel, evolutionarily conserved lncRNA VEAL2 is shown to inhibit PRKCB activity and junctional permeability in zebrafish and in human vascular endothelium. VEAL2 inhibits vascular permeability and modulates junctional assembly in zebrafish vasculature and in human endothelial cells. VEAL2 inhibits PRKCB activity by competing with diacylglycerol binding to its C1 domain. The levels of VEAL2 are reduced in retinal choroid tissue of patients with diabetic retinopathy. Ectopic expression of VEAL2 ameliorates the hyperglycemic disease pathophysiology in human endothelial cells. Abstract : The evolutionarily conserved lncRNA VEAL2 enhances junctional integrity in developing zebrafish vasculature and in hyperglycemic vascular endothelium in humans.